Analisis Pemanfaatan Pelayanan Pertolongan Persalinan Non Tenaga Kesehatan oleh Ibu Bersalin di Kabupaten Kolaka Timur (Studi Kasus di Puskesmas Ueesi) - Muh. Ridha Setiawan Salam; Sutopo Patria Jati; Sri Achadi Nugraheni (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
Traditional services or service by dukun is a phenomenon of community tradition that needs to be evaluated, especially related to birth assisstance. The scope of delivery by health workers was still low of 68% in 2016.This was qualitative research with phenomenological approach. The subjects of this study were maternal mothers who gave birth within the last 1 (one) year selected from the highland region and lowland region in the Uesesi Puskesmas area. Data were collected by in-depth interview techniques. Processing and data analysis using content analysis. Results showed that there were predisposition factors, enabling factors and reinforcing factors which influenced the behavior. The predisposition factors were 1) the informant is able to explain about healthy labor but unable to explain the safe delivery 2) The informant is still more inclined to the service of dukun maternity 3) The high trust of informant to the dukun maternity. The enabling factors were 1) access to utilize the service of dukun maternity is easy because dukun apply method